2005
DOI: 10.1093/ejo/cji004
|View full text |Cite
|
Sign up to set email alerts
|

The psychosocial effects of cleft lip and palate: a systematic review

Abstract: This systematic review examined the published scientific research on the psychosocial impact of cleft lip and palate (CLP) among children and adults. The primary objective of the review was to determine whether having CLP places an individual at greater risk of psychosocial problems. Studies that examined the psychosocial functioning of children and adults with repaired non-syndromal CLP were suitable for inclusion. The following sources were searched: Medline (January 1966-December 2003), CINAHL (January 1982… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
411
3
19

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 384 publications
(454 citation statements)
references
References 36 publications
21
411
3
19
Order By: Relevance
“…Older subjects were 25% more likely to have high OHRQoL scores, indicating a negative impact of cleft lip and/or palate. A study showed that younger individuals experienced worse quality of life [21]. However, the association between age and quality of life remains controversial in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Older subjects were 25% more likely to have high OHRQoL scores, indicating a negative impact of cleft lip and/or palate. A study showed that younger individuals experienced worse quality of life [21]. However, the association between age and quality of life remains controversial in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…These children are teased about their cleft-related features such as speech, teeth, and lip appearance and lose self-confi dence. [5] India is one of the many regions of the world where documentation of the rates of birth anomalies is incomplete. Reliable and complete record of statistics is diffi cult because of the infrastructure and due to the association of craniofacial anomalies.…”
Section: Introductionmentioning
confidence: 99%
“…Reading disabilities, for example, may affect as many as 30% to 40% of children with ICLP [18,60]. In addition to the cognitive deficits, social dysfunction has been identified repeatedly and in high frequency in individuals with ICLP, as recently reviewed [38]. In general, individuals with ICLP are more likely to be socially inhibited or shy and report fewer friends than noncleft controls [17,31,41,42,50,58].…”
Section: Introductionmentioning
confidence: 99%